Influence of fiberglass and the additive chema estruct on the resistance of concrete f ́c 280 kg/cm2, Trujillo 2023 - Juárez Rodríguez, Elkin Ronaldo; Martell Ortiz, Juan Carlos; Noriega Vidal, Eduardo Manuel; Henríquez Ulloa, Juan Paul Edward; Valdivieso Velarde, Alan Yordan; Rodríguez Beltran, Eduar Jose (LACCEI, 2024)
Abstract– Given the problem of concrete, we sought to increase the compressive strength, analyzing its behavior by adding fiberglass and chema estruct so that it has better properties, for this reason the objective was to determine the influence of both additives on the resistance of concrete 280 kg/cm2. This research was called experimental-applied because it uses a quantitative approach. The doses used were 1.0%, 2.0% and 3.0% tested at ages of 3, 7, 14 and 28 days, 12 standard specimens were tested, 36 of each additive and 108 with combinations of both additives. The effects achieved by adding fiberglass in a dose of 2.0% improve the unit weight, temperature, compression, but the workability decreases, using chema estruct the workability, temperature, unit weight and compression improve with a dose of 3.0%, the tests at compression of 28 days with the standard specimens obtained a resistance of 282.40 kg/cm2, adding fiberglass resistances of 192.38 kg/cm2, 310.67 kg/cm2 and 301.50 kg/cm2. Using chema estruct resistances of 293.74 kg/cm2, 303.84 kg/cm2 and 333.72 kg/cm2. Likewise, when making combinations, the most favorable result was adding 2.0% FV + 3.0% ChE, obtaining resistance of 364.32 kg/cm2. Concluding that both additives positively influence the concrete.